The Relation between the Socio-Economic Status and the Motivation to Learn of the Pupils in the High Schools in the Triangle Area of Israel - Kiedan, Fedaa Mohammad (Journal of Educational and Psychological Sciences, 2022)
This research aimed to examine the relationship between the socio-economic status (SES) and Motivation to learn. A quantitative research method was used. A simple random selection method was used where 242 male and female students aged between 15 – 18 years old selected and 110 parents. The study used questionnaires that were distributed to a large number of High school students of the Arab sector in the Triangle area in Israel. Many variables such as income, family status, house (property or rent), economic situation, parental education level, parental involvement alongside many other factors were analysed to assess the SES. The research was based on the Social Capital Theory and the Success Model that showed the relationship between variables.The statistical analysis conducted was R programming language via R Studio. Further analysis using statistics such as t, F, Cramer v, Pearson correlation were used to measure the relationships between the different variables.The results have shown that there is a positive relationship between the socio-economic status of Arab families and the student's motivation to learn. The research also indicated that academic achievement is affected by and shows a reciprocal relationship with three variables: well-being, achievement, and socio-economic status.
Keywords: The Socio-Economic Status (SES); Motivation; Academic Achievement; Social Well-Being